CUZD1 and Anti-CUZD1 Antibodies as Markers of Cancer and Inflammatory Bowel Diseases - Christos Liaskos; Eirini I. Rigopoulou; Timoklia Orfanidou; Dimitrios P. Bogdanos; Christos N. Papandreou (Clinical and Developmental Immunology)
CUZD1, the CUB, and zona pellucida-like domains-containing protein 1, is a newly identified antigen of pancreatic autoantibodies (PAB) giving a reticulogranular pattern in patients with inflammatory bowel diseases, and in particular Crohn’s disease. The exact mechanisms by which this pancreatic antigen becomes the target of IBD-specific pancreatic autoantibodies are unclear. At the same time, evolving data strongly support a role for CUZD1 in carcinogenesis. Human CUZD1 is mapped at chromosome 10q26.13 and the loss of this region is a frequent event in various malignant tumours. mRNA overexpression of CUZD1 has been noted in ovarian cancer and serum levels of CUZD1 are elevated in women with ovarian cancer and patients suffering from pancreatic cancer. CUZD1 appears to be one of the relatively few biomarkers that serve as both cancer biomarker and autoantigen of autoantibodies in an autoimmune disease unrelated to cancerous organs. This review discusses the role of CUZD1 in cancer and autoimmunity. We anticipate that a better understanding of the function of CUZD1 will help us to understand how it becomes the focus of an autoimmune attack specifically targeting the intestine and its enigmatic role in carcinogenesis.